2011
DOI: 10.1016/j.ssresearch.2010.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem and mastery trajectories in high school by social class and gender

Abstract: Using longitudinal data from 769 white adolescents in the Midwest, this research applies a social structure and personality perspective to examine variation in self-esteem and mastery trajectories by gender and SES across the high school years. Analyses reveal that high SES adolescents experience significantly steeper gains in self-esteem and mastery compared to low SES adolescents, resulting in the reversal of SES differences in self-esteem and the emergence of significant SES differences in mastery. Pre-exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 64 publications
1
36
0
1
Order By: Relevance
“…Adolescent boys had stronger mastery beliefs than their female age-peers; this was true of the cohort their parents were part of as well (Falci 2011). There were no significant gender differences in generalized life expectations, but there was a small significant difference by age, with older youth less optimistic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescent boys had stronger mastery beliefs than their female age-peers; this was true of the cohort their parents were part of as well (Falci 2011). There were no significant gender differences in generalized life expectations, but there was a small significant difference by age, with older youth less optimistic.…”
Section: Resultsmentioning
confidence: 99%
“…Past research finds socioeconomic status to be positively related to adolescents' mastery beliefs and generalized life expectations (Conger et al 2009; Johnson and Hitlin 2017; Lewis, Ross & Mirowsky 1999), and the current study also found this pattern in a relatively disadvantaged sample. Parent-child relationships matter as well, though prior research has focused much more so on mastery beliefs than generalized life expectations and other optimism-related concepts (Ben-Zur 2003; Falci 2011; Finch et al 1991; Hasan and Power 2002; Nurmi and Pulliainen 1991; Whitbeck et al 1997). As such, this study builds the base of knowledge about parenting and optimistic expectations as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, female but not male students were found to benefit from the training programmes. A recent longitudinal study among white adolescents in the Midwest applied a social structure and personality perspective to examine variations in self-esteem and mastery trajectory by gender [35]. It was concluded that self-esteem increases at a faster rate among girls than boys during high school.…”
Section: Discussionmentioning
confidence: 99%
“…While there are other sources of mastery such as vicarious experience, verbal persuasion, and emotional arousal, personal accomplishments usually serve as the foundation for feelings of mastery among adults (Bandura 1977). Levels of mastery can be influenced by a variety of factors such as negative views of one's environment, neighborhood disorder (Mizell and Erickson 2007), income and education levels (Bird and Ross 1993;Downey and Moen 1987;Falci 2011;Pearlin et al 1981), ethnicity (Mirowsky and Ross 1989;Mizell 1999), and gender (Cassidy and Davies 2003). Further, research demonstrates that it is our perception of our situation, rather than our objective circumstances, that lead us to feel masterful and efficacious (Latkin and Curry 2003;Ross 2000).…”
Section: Masterymentioning
confidence: 99%